ON SQUARE ROOT OF STURM-LIUVILLE OPERATOR - А.Sh. Shaldanbayev; А.А. Shaldanbayevа; B.А. Shaldanbay (Academic Scientific Journal of Computer Science, 2019)
In this paper, we find square root of the Sturm – Liouville operator and show that this root is a functional-differential operator of first-order. Form of the corresponding boundary problem of this functional - differential equation is found. As a suggestive idea, we use one Putnam theorem. Boundary value conditions of the Sturm-Liouville operator have a very special form, and they are dictated by the method of investigation. The found unitary operator generalizes the known momentum operator.